Stereotactic Body Radiation Therapy With Simultaneous Integrated Boost in Patients With Spinal Metastases. (24th April 2020) - Pontoriero, Antonio; Iatì, Giuseppe; Cacciola, Alberto; Conti, Alfredo; Brogna, Anna; Siragusa, Carmelo; Ferini, Gianluca; Davì, Valerio; Tamburella, Consuelo; Molino, Laura; Cambareri, Domenico; Severo, Cesare; et al.
Stereotactic body radiation therapy in patients with spine metastases maximizes local tumor control and preserves neurologic function. A novel approach could be the use of stereotactic body radiation therapy with simultaneous integrated boost delivering modality. The aim of the present study is to report our experience in the treatment of spine metastases using a frameless radiosurgery system delivering stereotactic body radiation therapy–simultaneous integrated boost technique. The primary endpoints were the pain control and the time to local progression; the secondary ones were the overall survival and toxicity. A total of 20 patients with spine metastases and 22 metastatic sites were treated in our center with stereotactic body radiation therapy–simultaneous integrated boost between December 2007 and July 2018. Stereotactic body radiation therapy–simultaneous integrated boost treatments were delivered doses of 8 to 10 Gy in 1 fraction to isodose line of 50%. The median follow-up was 35 months (range: 12-110). The median time to local progression for all patients was not reached and the actuarial 1-, 2-, and 3-years local free progression rate was 86.36%. In 17 of 20 patients, a complete pain remission was observed and 3 of 20 patients had a partial pain remission (complete pain remission + partial pain remission: 100%). The median overall survival was 38 months (range 12-83). None of the patients experienced neither radiation adverse events (grade 1-4) nor reported pain flair reaction. None of the patients included in our series experienced vertebral compression fracture. Spine radiosurgery with stereotactic body radiation therapy–simultaneous integrated boost is safe. The use of this modality in spine metastases patients provides an excellent local control.